Examining the Impact of the Boycott Movement on Starbucks Stock Trading Volume: The Role of Market Returns and Trading Volume Persistence - Erna Hayati (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The Boycott, Divestment, and Sanctions (BDS) movement, which intensified following the escalation of the Israel-Palestine conflict on 7 October 2023, has increased investors' attention to companies alleged to have affiliations with Israel, including Starbucks. This study aims to analyze the effect of the boycott movement on Starbucks stock trading volume while controlling for lagged stock trading volume and market return. The study uses daily data for one year before and one year after the boycott movement, covering the period from 7 October 2022 to 7 October 2024, with a total of 502 observations. The analysis employs multiple linear regression. Before model estimation, descriptive analysis and a stationarity test using the Augmented Dickey-Fuller (ADF) test were conducted. Initial estimation was performed using Ordinary Least Squares (OLS), followed by diagnostic tests. Because the OLS model indicated heteroskedasticity and autocorrelation, the final estimation employed the Newey-West Heteroskedasticity and Autocorrelation Consistent (HAC) method to obtain robust standard errors. The results show that the boycott movement has a positive and significant effect on Starbucks stock trading volume. In addition, lagged stock trading volume also has a positive and significant effect, indicating persistence in stock trading activity. By contrast, market return, proxied by the daily return of the NASDAQ index, has no significant effect on Starbucks stock trading volume. These findings indicate that, during the study period, Starbucks stock trading activity was influenced more by company-specific factors associated with the boycott movement than by general market conditions. This study provides empirical evidence that non-financial events arising from geopolitical dynamics can influence investor behavior by increasing stock trading activity.